Co-creation of a gender responsive TB intervention in Nigeria: a researcher-led collaborative study - Chukwuebuka Ugwu; Oluwatoyosi Adekeye; Beate Ringwald; Rachael Thomson; Obioma Chijioke-Akaniro; Chukwuma Anyaike; S Bertel Squire; John Bimba; Tom Wingfield (BMC Health Services Research)
Abstract Background In Nigeria, men constitute over half of the people notified with tuberculosis (TB), experience longer delays before reaching care, and are estimated to account for two thirds of people who miss out on care. The higher TB risk and burden in men has implications for the whole population and reaching them earlier with TB services will reduce onward transmission in households, communities, and workplaces. The absence of a comprehensive guidance and the lack of substantial empirical evidence on TB care approaches that are responsive to the needs of men in Nigeria exacerbates this problem. Therefore, this research aimed to co-create a gender-responsive intervention for men in peri-urban communities in Nigeria. Methods Our study utilised a researcher-led collaborative approach to engage local TB stakeholders including communities adversely affected by the disease to co-create a gender-responsive TB intervention. Between March and November 2022, we engaged 13 local TB stakeholders in a three-phase participatory intervention design process. This engagement involved two iterative cycles of Delphi research online, and an in-person workshop. In the first and second phases, participants described the potential impact of 15 listed interventions and prioritised combinations of nine interventions deemed to be effective in overcoming identified gendered barriers. Responses were analysed using a combination of qualitative framework approach, content analysis, and summary descriptive statistics assisted by NVivo software. Stakeholder consensus on a preferred intervention package was reached during the participatory workshop. Results Overall, participants prioritised approaches that sought to actively find and systematically screen men for TB including awareness creation as a crucial component. The stakeholders placed significant considerations on the synergy between interventions and their programmatic sustainability when making their final choices. Consequently, a complex intervention package comprising three components was developed. These included targeted awareness creation among men in communities; TB screening in male-dominated socio-cultural congregate settings; and the use of digital chest X-ray screening. Anticipated early outputs of this intervention included improved TB knowledge, increased care-seeking, reduced TB-related costs and TB stigma, and accelerated early diagnosis among men in Nigeria. Conclusion Leveraging the insights and experiences of local stakeholders through iterative engagements yielded consensus on a viable gender-responsive TB intervention.